Economy-wide effects of the land redistribution policies in Thailand: a computable general equilibrium model - Piyajitmetta, Pawarid; Puttanapong, Nattapong (Letters in spatial and resource sciences, 2025)
This study analyzes the economy-wide effects of land redistribution policies in Thailand using a computable general equilibrium model. We isolate the role of land in perpetuating income inequality by disaggregating land rent from capital returns in a social accounting matrix. Three policy scenarios are evaluated: (1) taxation of land income, (2) land tenure reform, and (3) redistribution of unused state-owned agricultural land. Results show that all scenarios reduce income inequality, although with varying fiscal and economic outcomes. Scenario 1, which taxes land income, is a highly efficient policy, achieving significant reductions in the income ratio and Gini coefficient without altering the land ownership structure. Scenario 2, which implements land tenure reform, leads to smaller inequality reductions due to the need for government compensation to the richest households for expropriated land. Scenario 3, which distributes unused state-owned agricultural land, provides the greatest benefits to the agricultural sector, improves food security, and reduces inequality, similar to Scenario 1. These findings offer valuable insights for policymakers in Thailand, emphasizing the potential for land redistribution to address income inequality while maintaining fiscal sustainability.